Experimental study of the adaptive gain feature for improved position-sensitive ion spectroscopy with Timepix2. (1st January 2022) - Bergmann, B.; Smolyanskiy, P.; Burian, P.; Pospisil, S.
Abstract: In the present work, we study the Timepix2 pixels' high energy response in the so-called adaptive gain mode. Therefore, Timepix2 with a 500 μm thick silicon sensor was irradiated with protons of energies in the range from 400 keV to 2 MeV and α -particles of 5.5 MeV from 241 Am. A novel method was developed to determine the energy deposit in single pixels of particle imprints, which are spread out over a set of neighbor pixels (cluster). We show that each pixel is capable of measuring the deposited energy from 4 keV up to ∼3.2 MeV. Reconstructing the full energy content of the clusters, we found relative energy resolutions ( σ E ) better than 2.7% and better than 4% for proton and α -particle data, respectively. In a simple experiment with a 5.5 MeV α -particle source, we demonstrate that energy losses in thin (organic) specimen can be spatially resolved, mapping out sample thickness variations, with a resolution around 1–2 μm, across the sensor area. The inherent spatial resolution of the device was determined to be 350 nm in the best case.